Diane Bell, Pat Caplan & Wazit Jahan Karim (eds.): Gendered Fields: Women, Men & Ethnography - Sørensen, Ninna Nyberg (Tidsskriftet Antropologi, 1993)
Diane Bell, Pat Caplan & Wazit Jahan Karim (eds.): Gendered Fields: Women, Men & Ethnography Anmeldes af Ninna Nyberg Sørensen